2020
DOI: 10.3390/ijms21124402
|View full text |Cite
|
Sign up to set email alerts
|

General and Target-Specific DExD/H RNA Helicases in Eukaryotic Translation Initiation

Abstract: DExD (DDX)- and DExH (DHX)-box RNA helicases, named after their Asp-Glu-x-Asp/His motifs, are integral to almost all RNA metabolic processes in eukaryotic cells. They play myriad roles in processes ranging from transcription and mRNA-protein complex remodeling, to RNA decay and translation. This last facet, translation, is an intricate process that involves DDX/DHX helicases and presents a regulatory node that is highly targetable. Studies aimed at better understanding this family of conserved proteins have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 174 publications
(267 reference statements)
2
39
0
Order By: Relevance
“…The recruitment of several eIF3 components also promoted the translation (Fig. 3d), supporting a previous finding that DHX29 cooperates with eIF3 during translation initiation 29,40 . Since several eIF3 components were also pulled down by 3ʹ-CiTIs (Fig.…”
Section: Trans-acting Factors Are Involved In 3ʹ-citi-mediated Translation Enhancementsupporting
confidence: 89%
See 2 more Smart Citations
“…The recruitment of several eIF3 components also promoted the translation (Fig. 3d), supporting a previous finding that DHX29 cooperates with eIF3 during translation initiation 29,40 . Since several eIF3 components were also pulled down by 3ʹ-CiTIs (Fig.…”
Section: Trans-acting Factors Are Involved In 3ʹ-citi-mediated Translation Enhancementsupporting
confidence: 89%
“…We further observed a direct interaction of DHX29 with HIF1A mRNAs (Extended data Fig. 9c), consistent with its general function as a subunit of the translation initiation complex 40 . Interestingly, the interaction between DHX29 and HIF1A mRNA was nearly eliminated by the 3ʹ-CiTI deletion under hypoxia, whereas this interaction was only reduced by ~50% during normoxia (Fig.…”
Section: ʹ-Citi and Dhx29 Promote Hif1a Translation In Response To Hypoxia In Vitro And In Vivosupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are also in line with those of a recent study, which reported that DDX5 suppresses IFN-I antiviral innate immune response by interacting with PP2A-Cβ to deactivate IRF3 [43]. However, because DDX is a large family of conserved RNA-binding proteins, nearly all DDX family members have been demonstrated to regulate cellular metabolism and maintain immune homeostasis through regulating nucleic acid binding and to modulate nucleic acid interactions and RNA-protein complex remodeling in host cells, such as DDX58, MDA5, DHX58, DDX3X, DDX21, DDX19, DDX39A, and DDX46 [2,13,14,15,16,[44][45][46][47][48][49][50][51]. In fact, DDX5 has been demonstrated to regulate transcription in order to play its roles in tumorigenesis, proliferation, differentiation, and metastasis pathways [30,46].…”
Section: Discussionmentioning
confidence: 99%
“…DDX3X and its orthologs, including Ded1 in Saccharomyces cerevisiae , are members of the DEAD-box family of RNA helicases, which have critical roles in many facets of RNA biology and gene expression (for review, see ( 12 )). While DDX3X/Ded1 has been implicated in a number of processes, it has been best characterized as a translation factor ( 13 , 14 ). Current models of eukaryotic translation initiation propose that translation factors, including the 40S ribosomal subunit, first assemble on the mRNA, and this preinitiation complex (PIC) then scans the mRNA, starting from the 5’ cap, for the start codon ( 15 ).…”
mentioning
confidence: 99%